2020
DOI: 10.1212/wnl.0000000000010463
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, major depressive disorder, and Alzheimer disease

Abstract: ObjectiveTo explore the causal relationships between sleep, major depressive disorder (MDD), and Alzheimer's disease (AD).MethodsWe conducted bi-directional 2-sample Mendelian randomisation analyses. Genetic associations were obtained from the largest genome-wide association studies currently available in UK Biobank (N = 446,118), the Psychiatric Genomics Consortium (N = 18,759), and the International Genomics of Alzheimer's Project (N = 63,926). We used the inverse variance weighted Mendelian randomisation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 49 publications
(88 reference statements)
5
34
5
1
Order By: Relevance
“…Apparent inconsistences between our nding and previous MR studies may be partly due to different de nitions, diagnostic criteria and forms of characterization of AD (such as cognitive impairment, memory loss, reaction time and so on) [53], different types of data (individual-level data or summary-level data) [53], different MR methods (linear MR or non-linear MR) [53], or different statistical analysis methods (genetic risk score) [54]. In addition, we found no causal relationship between AD and insomnia, whereas a recent MR study conducted by Huang et al found that higher risk of AD was associated with lower risk of insomnia (OR: 0.99, P IVW = 7 × 10 − 13 ) [55]. Given the consistency in population, sample size and statistical methods between the study by Huang et al and the present study, we consider that the difference in results is due to Huang et al adopted F-statistic > 10 to lter exposure-related SNPs to reduce the weak instrumental bias of using genotype data [55].…”
Section: Discussioncontrasting
confidence: 50%
“…Apparent inconsistences between our nding and previous MR studies may be partly due to different de nitions, diagnostic criteria and forms of characterization of AD (such as cognitive impairment, memory loss, reaction time and so on) [53], different types of data (individual-level data or summary-level data) [53], different MR methods (linear MR or non-linear MR) [53], or different statistical analysis methods (genetic risk score) [54]. In addition, we found no causal relationship between AD and insomnia, whereas a recent MR study conducted by Huang et al found that higher risk of AD was associated with lower risk of insomnia (OR: 0.99, P IVW = 7 × 10 − 13 ) [55]. Given the consistency in population, sample size and statistical methods between the study by Huang et al and the present study, we consider that the difference in results is due to Huang et al adopted F-statistic > 10 to lter exposure-related SNPs to reduce the weak instrumental bias of using genotype data [55].…”
Section: Discussioncontrasting
confidence: 50%
“…This speculation is supported by a recent Mendelian randomization (MR) analysis from the largest genome-wide association studies of the UK Biobank (N = 446,118), the Psychiatric Genomics Consortium (N = 18,759), and the International Genomics of Alzheimer's Project (N = 63,926). This MR analysis found that higher risk of AD, based on genetic risk score, was significantly associated with being a “morning person,” who prefers going to bed and waking earlier and is less active in the first half of the night ( 15 ). Other studies have reported the association between sleep timing and risk of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Values of p < 0.0004 in two-tailed tests were considered significant (p=0.05 with Bonferroni correction for 123 potential exposures). We estimated effect size globally and by time between health condition exposure and AD diagnosis, as follows: (0 -2] years, (2 -10] years, and (10)(11)(12)(13)(14)(15) years. In this last category, no health condition was found to increase the risk of AD onset in both countries.…”
Section: Discussionmentioning
confidence: 99%
“…The lateness of these associations suggests that these conditions are probably prodromal symptoms of the disease rather than risk factors. For instance, a recent Mendelian randomised study 12 showed that AD was more likely to be the cause of sleep disorders rather than a consequence of these disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation